Self-consumption enhancement and peak shaving of residential photovoltaics using storage and curtailment. (1st October 2016) - Luthander, Rasmus; Widén, Joakim; Munkhammar, Joakim; Lingfors, David
Abstract: Increasing the self-consumption of photovoltaic (PV) power is an important aspect to integrate more PV power in the power system. The profit for the PV system owner can increase and the stress on the power grid can be reduced. Previous research in the field has focused on either self-consumption of PV power in individual buildings or PV power curtailment for voltage control. In this paper self-consumption of residential PV power in a community of several single-family houses was investigated using high-resolution irradiance and power consumption data. Cases with individual or shared battery energy storages for the houses were examined. PV power curtailment was investigated as a method to reduce feed-in power to the grid, i.e. peak shaving. Results indicated that the self-consumption ratio increased when using shared instead of individual storage. Reducing the feed-in power from the community by almost 50% only led to maximum 7% yearly production losses due to curtailment and storage losses. The economics for shared storage are slightly better than for individual ones. These results suggest that residential PV-battery systems should use ( i ) shared energy storage options if local regulations allow it and ( ii ) PV power curtailment if there are incentives to lower the feed-in power. Highlights: High increment in PV self-consumption in a community using shared grid connection. Higher self-consumption with centralized than individual battery storage in houses. Halving of peak power to grid by PV power curtailment with annual losses below 7%. Higher annual revenue from shared than individual battery storage.